Synthesis of Star 6-Arm Polyethylene Glycol-Heparin Copolymer to Construct Anticorrosive and Biocompatible Coating on Magnesium Alloy Surface - Hong, Qingxiang; Zhou, Hualan; Cheng, Yuxin; Yang, Minhui; Zhang, Qiuyang; Liu, Sen; Xiong, Qingping; Pan, Changjiang (Frontiers in Bioengineering and Biotechnology, 2022)
Magnesium alloy has become a research hotspot of the degradable vascular stent materials due to its biodegradability and excellent mechanical properties. However, its rapid degradation rate after implantation and the limited biocompatibility restrict its application in clinic. Constructing a multifunctional bioactive polymer coating on the magnesium alloys represents one of the popular and effective approaches to simultaneously improve the corrosion resistance and biocompatibility. In the present study, the copolymer of 6-arm polyethylene glycol (PEG) and heparin (PEG-Hep) was successfully synthesized and then immobilized on the surface of chitosan (Chi)-modified magnesium alloy surface through electrostatic interaction to improve the corrosion resistance and biocompatibility. The results of attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) showed that a dense and compact coating was created on the magnesium alloy surface. The coating displayed excellent hydrophilicity. At the same time, the as-prepared coating can significantly not only improve the corrosion potential, reduce the corrosion current and the pH changes of the immersion solution, but also keep a relatively intact surface morphology after immersing in SBF (simulated body fluid) solution for 14 days, demonstrating that the coating can significantly improve the corrosion resistance of the magnesium alloy. Moreover, the magnesium alloy with PEG-Hep coating exhibited excellent hemocompatibility according to the results of the hemolysis rate and platelet adhesion and activation. In addition, the modified magnesium alloy had a good ability to promote the endothelial cell adhesion and proliferation. Therefore, the PEG-Hep multifunctional coating can be applied in the surface modification of the biodegradable magnesium alloy stent to simultaneously improve the corrosion resistance and biocompatibility.